Formulation and Evaluation of Spirulina and Charcoal Peel off Mask - Jadhav Dnyaneshwari Prabhakar; Bhalke Rasika Dnyandeo; Giri Mahendra Ashok; Tekale Pratiksha Nanasaheb; Chatur Sneha Nanasaheb; Erande Aishwarya Arun (Asian Journal of Pharmaceutical Research and Development, 2026)
The increasing preference for natural and eco-friendly cosmetic products has led to the exploration of bioactive ingredients for skincare applications. the present study aims to formulate and evaluate a peel-off face mask incorporating spirulina and activated charcoal as key functional components. spirulina, a blue-green microalga, is rich in proteins, vitamins, and antioxidants, which contribute to skin nourishment, hydration, and protection against oxidative stress. activated charcoal is well known for its excellent adsorptive properties, enabling effective removal of dirt, toxins, and excess oil from the skin. The peel-off mask was formulated using polyvinyl alcohol as a film-forming agent, along with suitable excipients such as glycerin as a plasticizer, humectants, and preservatives to enhance stability and usability. the prepared formulation was evaluated for various physicochemical parameters including ph, viscosity, spreadability, drying time, and film-forming characteristics. stability studies and skin irritation tests were also conducted to ensure product safety and effectiveness. Herbal spirulina peel-off mask showed satisfactory evaluation tests, spreadability was 9.7, peelability 18 min, goodstability, and no skin irritation. The formulation with skin-friendly pH 5.6 provided effective cleansing, hydration, and nourishment for healthy skin.